2020
DOI: 10.1111/ajt.15738
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of kidney transplant failure based on urine

Abstract: In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…However, due to the invasive nature of the procedure serious complications may arise, in rare cases even resulting in the loss of the transplant. Furthermore, from our experience (this study and [15]) many standard transplant biopsies deliver very little DNA and are frequently cross‐contaminated with recipient tissue, which may be perirenal fat or recipient derived blood and immune cells. Based on STR analysis, this ‘contamination’ of donor with recipient DNA can reach approximately 50% (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the invasive nature of the procedure serious complications may arise, in rare cases even resulting in the loss of the transplant. Furthermore, from our experience (this study and [15]) many standard transplant biopsies deliver very little DNA and are frequently cross‐contaminated with recipient tissue, which may be perirenal fat or recipient derived blood and immune cells. Based on STR analysis, this ‘contamination’ of donor with recipient DNA can reach approximately 50% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy cylinder was immediately stored at À80 °C and DNA was extracted subsequently. Another option was expanding donor tubular cells from the recipients' urine as described earlier [15,16]. Human urinary Primary Tubular Cells (huPTC) were cultured over a period of 3 weeks, with two passages until a confluent 10 cm 2 culture dish was available for DNA extraction (Fig.…”
Section: Establishment Of Collecting Donor Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The third ADTKD- MUC1 patient is a direct descendent of the individual ADTKD-0145 (family A-30) published by Wenzel et al, in whom the mutation has been confirmed ( Wenzel et al, 2018 ). Cells were cultured according to established protocols ( Keller et al, 2012 ; Wiesener et al, 2020 ). Tubular cells were exposed to HIF stabilizers (concentrations used were: DMOG 1 mM, Daprodustat 100 μM, Molidustat 100 μM, Vadadustat 100 μM, Roxadustat 100 μM or as indicated), hypoxia (1% O 2 or control conditions [20.9% O 2 , no treatment]) for 16 h.…”
Section: Methodsmentioning
confidence: 99%